EKOSISTEM MANGROVE TANJUNG JABUNG BARAT DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR - Muhammad Toto Nugroho; Nurlaili Mulyani; Siti Muhayyah Alawiyah; Pandu Adi Cakranegara; Purniadi Putra (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
Local wisdom provides many benefits not only for the community around the local wisdom environment but is also able to provide excellent benefits in the current learning process. This study aims to integrate local wisdom of the mangrove ecosystem in West Tanjung Jabung Regency in learning in elementary schools. The research method used is descriptive qualitative with ethnographic research type. The informants used in this study found 6 people, namely 3 community leaders and 3 grade VI elementary school teachers. Data collection techniques in this study used observation, interviews, and document studies. The data analysis technique adopted the techniques from Miles and Hubberman, namely data reduction, data presentation, and conclusion drawing. The result of this research is that local wisdom of the mangrove ecosystem in West Tanjung Jabung Regency can be integrated in class VI learning, theme 1, sub-theme 1, learning 1 and is able to increase students' knowledge and foster good character for elementary school students.